Airflow restriction mask induces greater central fatigue after a non-exhaustive high-intensity interval exercise - Da Silva, K. J.; Silva, L. C.; Felippe, L. C.; Silva-Cavalcante, M. D.; Franco-Alvarenga, P. E.; Learsi, S.; Ataide-Silva, T.; Bertuzzi, R.; Lima-Silva, A. E.; Ferreira, G. A. (Scandinavian Journal of Medicine & Science in Sports, 2022)
The airflow restriction mask (ARM) is a practical and inexpensive device for respiratory muscle training. Wearing an ARM has recently been combined with high-intensity interval exercise (HIIE), but its effect on neuromuscular fatigue is unknown. The present study investigated the effects of ARM wearing on neuromuscular fatigue after an HIIE session. Fourteen healthy men performed two HIIE sessions (4x4min at 90% HRmax, 3min recovery at 70% HRmax) with or without an ARM. Neuromuscular fatigue was quantified via pre- to post-HIIE changes in maximal voluntary contraction (MVC), voluntary activation (VA, central fatigue), and potentialized evoked twitch force at 100, 10, and 1 Hz (peripheral fatigue). Blood pH and lactate were measured before and after the HIIE session, while HR, SpO2, dyspnea, physical sensation of effort (P-RPE), and Task Effort and Awareness (TEA) were recorded every bout. The exercise-induced decrease in MVC was higher (p<0.05) in the ARM (-28±12%) than in the control condition (-20±11%). The VA decreased (p<0.05) in the ARM (-11±9%) but not in the control condition (-4±5%, p>0.05). Pre- to post-HIIE declines in evoked twitch at 100, 10, and 1 Hz were similar (p>0.05) between ARM and control conditions (ARM: -18±10, -43±11 and -38±12%; Control: -18±14, -43±12 and -37±17%). When compared with the control, the HIIE bout wearing ARM was marked by higher heart rate, plasma lactate concentration, dyspnea, P-RPE and TEA, as well as lower SpO2 and blood pH. In conclusion, ARM increases perceptual and physiological stress during a HIIE, which may lead to a greater post-exercise central fatigue.